2005
DOI: 10.1016/j.msec.2005.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of cobalt into ZnO nanoclusters

Abstract: The structural, optical and magnetic properties of nanostructured ZnO films co-doped with cobalt and aluminium have been studied. The nanocrystalline films, with cluster sizes in range 50 - 100 nm, were deposited by pulsed laser ablation in a mixed atmosphere of oxygen and helium. The nanocrystallites have the wurtzite structure and are highly oriented with the c-axis perpendicular to the substrate. Both optical and electron spin resonance (ESR) spectroscopy results show the substitutional incorporation of Co$… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…7-9͒ in which Co is substituted for Zn rather than forming clusters. These studies also show that nanocrystalline Zn 1−x Co x O is paramagnetic in this concentration range and at low temperature; 8,9 ferromagnetism was observed only at very low temperature. Another agent must therefore be responsible for promotion of high-T c ferromagnetism in Zn 1−x Co x O.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…7-9͒ in which Co is substituted for Zn rather than forming clusters. These studies also show that nanocrystalline Zn 1−x Co x O is paramagnetic in this concentration range and at low temperature; 8,9 ferromagnetism was observed only at very low temperature. Another agent must therefore be responsible for promotion of high-T c ferromagnetism in Zn 1−x Co x O.…”
Section: Introductionmentioning
confidence: 54%
“…Recent magnetic resonance, [27][28][29][30][31][32] carrier mobility, 33 positron annihilation spectroscopy, 34 and first-principles calculations [35][36][37] have given a fuller picture of defect-induced electronic states in ZnO. Magnetic resonance techniques 8,9,38 have been applied to Zn 1−x Co x O and Zn 1−x Mn x O films and nanoclusters. As noted above, these studies 8,9,38,39 as well as x-ray magnetic circular dichroism, 12,39 which probe the local crystal structure about the transition-metal ion, have concluded that the transition-metal ions substitute for a Zn ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed RTFM in hydrogenated samples was attributed either to the appearance of Co clusters [3] or oxygen vacancies [4]. Nanocrystals of ZnO:Co are reported to be paramagnetic [5,6], ferromagnetic [7,8] or superparamagnetic [9]. In the present work, we report the observation and possible explanation of intrinsic RTFM in chemically synthesized nanocrystalline ZnO:Co samples having cobalt concentration ranging from 1 to 10 at%.…”
Section: Introductionmentioning
confidence: 71%
“…Co 2 þ -doped ZnO nanoparticles are prospective DMS candidates, and have been investigated extensively . EPR studies of the Co 2 þ ion in magnetic semiconductors, such as SnO 2 [26], provide information on the magnetic state of this compound, and its behavior under different synthesis conditions [1,[16][17][18][19][20][21][22][23][24][25]. The main conclusions of these investigations are: (i) there are present both localized Co 2 þ ions and ferromagnetically coupled Co 2 þ ions in the host material; (ii) The spin-Hamiltonian (SH) parameters for the Co 2 þ ion are very close to those for Co 2 þ -substituted ZnO crystal, characterized by highspin Co 2 þ ions; (iii) there is exhibited an electron paramagnetic resonance (EPR) signal due to Co 2 þ ions, situated in distorted local environment, characterized by high-spin Co 2 þ ions.…”
Section: Introductionmentioning
confidence: 99%